A review of electrical characterization techniques for ultrathin FDSOI materials and devices. (March 2016) - Cristoloveanu, Sorin; Bawedin, Maryline; Ionica, Irina
Abstract: The characterization of nanosize SOI materials and devices is challenging because multiple oxides, interfaces and channels coexist. Conventional measurement methods need to be replaced, or at least updated. We review the routine techniques that proved efficient for the evaluation of bare SOI wafers (essentially the pseudo-MOSFET) and of MOS structures (transistors and gated diodes). Informative examples are selected to illustrate the typical properties of advanced SOI wafers and MOSFETs. We will show how the ultrathin film and short-channel effects affect the interpretation of the experimental data.